High prevalence of Blastocystis spp. in children from a periurban school - Quispe Juli, Cender Udai (2016)
Introduction. Intestinal parasitosis is a serious public health problem in developing countries, and blastocystosis is an emerging parasitosis. Objectives. To determine the prevalence of infection by Blastocystis spp. and other intestinal parasites in children from a periurban school. Design. Observational and transversal study. Location. A school located in the district of Yura in Arequipa, Peru. Participants. 83 children between 4 and 8 years old. Interventions. Stool samples obtained from the children were analyzed with the modified Telemann method; a descriptive analysis was done by calculating frequency. Main outcome measures. Presence of the intestinal parasite. Results. The prevalence of Blastocystis spp. was 81.9% (68/83), the overall prevalence of parasites was 96.4% (80/83), and 80.7% (67/83) had more than ne type of parasite. Conclusions. There was a high prevalence of Blastocystis spp. and other intestinal parasites in the sample studied. There was also a high polyparasitism in the school population studied. This is the first study in this community.